“Balanced Scorecard y el volumen de ventas en las empresas de artículos de ferreterías y revestimiento de pisos del Cantón La Maná, año 2021 - Lozano Montero, Vanessa Edelmira (2021)
Currently in the business world, so full of changes and so highly competitive, microenterprises must devote significant resources of time, energy, human, financial to measure the work they do to achieve their strategic objectives, the problem arose because most are limited to do just that to use the empirical method that does not allow to develop specifically in the economic process and the lack of knowledge in work performance, customer service, and marketing strategies make microenterprises fail to establish and maintain themselves in the market competing. The objective is to implement the balanced scorecard in the volume of sales in the hardware and floor covering companies for the development of innovative strategies in Canton La Maná, to fulfill this purpose we resorted to bibliographic and field research, because more and more microenterprises conclude that measuring the results of their activity is more crucial than ever, but the systems they use to collect, monitor and share information on results contain many flaws and the balanced scorecard comes to revolutionize in seeking to achieve a goal. The population universe of 2,740 commercial microenterprises and 1,668 collaborators in the urban sector was taken as a base, applying the calculation of the sampling by strata, a sample of 204 clients and 36 owners was obtained, to whom the surveys were applied and whose instrument was the questionnaire that was validated. The most relevant findings indicated that there is a relationship of 0.812 according to the balanced scorecard factors (knowledge, business philosophy, innovation, motivation, opportunities and strategies) and sales volume (sales prospects, level of satisfaction, innovation, infrastructure, product and customer service) demonstrating that the balanced scorecard is of vital importance. It is concluded that the balanced scorecard has an impact on the sales volume in the companies so that with the results it was proposed that with adequate knowledge of business philosophy, innovation, motivation, opportunities and strategies there will be an increase in the economy.